Prion infection of ovine cell culture with a natural Swedish scrapie isolate from 1986 - Ahlberg, Viktor (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2010)
Scrapie is an infectious neurologic disease in sheep caused by prions, corresponding to transmissible spongiform encephalopathies (TSEs) in other species. The prion is presumably constituted of PrPSc, the misfolded form of the normal endogenous prion protein, PrPC, which is found in practically all cells in the body. PrPSc can induce a conformational change in PrPC and misfold it as an imprint of itself; this is how prions amplify and spread. The process of conformational change is poorly understood and there might exist intermediate forms between PrPC and PrPSc. Bioassay using mice has traditionally been the golden standard in prion studies but is limited by cost and time. Cell culture studies are now used but often rely on using so called rodent-adapted strains and/or cells overexpressing the prion protein.